Sequenciamento parcial dos genes TOX e NCOA2 em bubalinos - De Camargo, G. [UNESP]; Cardoso, D. F. [UNESP]; Baldi, F. [UNESP]; Regitano, L.; Tonhati, H. [UNESP] (My University, 2015)
Buffaloes play an important role in food production and in the socioeconomic development of tropical regions. The characterization of genes permits the study of traits of this species and the development of animal production technology. This work partially studied the thymus high mobility group box protein (TOX) and the Nuclear Receptor Coactivator 2 (NCOA2) genes in female Murrah buffaloes using a PCR-sequencing technique. Six SNPs were identified in each gene. Two adjacent SNPs in TOX gene create/destroy a mature miRNA production site and are good candidates to be further studied. The homology of the regions of these genes with the cattle correspondents is very high (99%).
Partial sequencing of the TOX and NCOA2 genes in buffaloes
Keywords: Bubalus bubalis; miRNA; SNP; Transcription factors